一种自适应智慧教育云平台 (2024)
本发明公开了一种自适应智慧教育云平台，涉及教育推荐技术领域，包括：云端知识库，云端知识库中包含当前学习阶段已知的所有知识数据；能力评定模块用于，评估学生各学科能力指标；偏好同步模块用于获取学生的偏好目标；关联性评估模块用于分析学生的学科能力指标与学生的偏好目标之间关联系数；措施同步模块用于获取实时教育变化；个性化推荐模块用于建立个性化教育资源推荐模型，生成若干个教育资源方案；最优教育资源筛选模块用于基于若干个教育资源方案，评估每一个教育资源方案的效益得分，并进行排序筛选，得到最优教育资源方案。本发明的优点在于：为学生提供长远发展目标与学习生涯规划的可能性。 The invention discloses a self-adaptive intelligent education cloud platform, and relates to the technical field of education recommendation, and the platform comprises a cloud knowledge base which comprises all knowledge data known in a current learning stage; the ability evaluation module is used for evaluating ability indexes of each subject of the student; the preference synchronization module is used for acquiring a preference target of the student; the relevance evaluation module is used for analyzing a relevance coefficient between the subject ability indexes of the students and the preference targets of the students; the measure synchronization module is used for acquiring real-time education changes; the personalized recomm